Screening and Identification of Indigenous Entomopathogenic Fungal Isolates from Agricultural Farmland Soils in Nile Delta, Egypt - Alsayed Alfiky (Journal of Fungi, 2022)
The compound negative impact of insect pests attacking agricultural ecosystems includes (i) direct yield losses from damaged crops, (ii) the economic cost of the attempt to prevent these losses and (iii) the negative short- and long-term hazard effects of chemical pesticides on human and environmental health. Entomopathogenic fungi (EMPF) are a group of microorganisms that represent the natural enemies of a number of crop pests, presenting an opportunity to harness their evolutionary fine-tuned relationship with their insect hosts as biocontrol agents in integrated pest management programs. The aim of this study was to establish an indigenous EMPF collection via the Galleria mellonella (greater wax moth) entrapment method from the soils of Nile Delta, Egypt. Obtained insect associated fungal isolates were bio-assayed for pathogenicity against the serious pest Spodoptera litura and Tenebrio molitor, and the seven outperforming isolates were selected for molecular identification and thermotolerance assay. Based on ITS sequence analysis and phylogeny, selected isolates were identified as Beauveria bassiana (four isolates), Metarhizium anisopliae (two isolates) and one isolate of Cordyceps javanica. The obtained results demonstrated (i) the efficacy of using insect baiting coupled with molecular identification and pathogenicity screening to isolate EMPF to control insect pests, and (ii) the availability of indigenous virulent EMPF in Nile Delta’s soil, which can be exploited for the development of sustainable crop protection strategies.